2017
DOI: 10.4163/jnh.2017.50.6.578
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary sodium intake and adiposity, inflammation, and hormone markers: A preliminary study

Abstract: Purpose: Excess intake of sodium is a major diet-related risk factor for human diseases including hypertension and cancer as well as obesity and inflammation. However, findings are still controversial, and evidence is lacking in Koreans. Therefore, for better understanding of the role of dietary sodium intake in disease etiology, this study investigated the effects of dietary sodium intake on adiposity, inflammation, and hormones in Koreans. Methods: A total of 80 males and females joined the study. The genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Fifty-nine cross-sectional studies reported on the association between sodium intake and a measure of adiposity (Table S3) (9-12, 35, 51-104) , 33 of these were included in meta-analyses (9-11, 53, 59, 60, 62, 63, 65-67, 69-71, 73, 75, 76, 79, 80, 83, 85, 88, 91, 93, 95, 97-104) . Reasons for exclusion from metaanalyses included; findings were only presented as correlation coefficients (n=16) (35, 54-56, 61, 68, 77, 78, 81, 82, 84, 86, 87, 90, 92, 96) or as standardised regression coefficients (n=4) (57,64,89,94) , the exposure variable was presented as sodium density (n=2) (12,72) or 24-hr urinary sodium excretion was reported as sodium concentration (mmol/L) (74) or on a logarithmic scale (52,58) . Of the studies included in meta-analyses, 14 were from Asia (62,63,66,69,70,73,75,76,83,85,91,97,100,101) , eight from USA (10,11,59,60,71,88,102,103) , five from South and Central America (53,65,79,80,93) , four from Europe (9,67,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty-nine cross-sectional studies reported on the association between sodium intake and a measure of adiposity (Table S3) (9-12, 35, 51-104) , 33 of these were included in meta-analyses (9-11, 53, 59, 60, 62, 63, 65-67, 69-71, 73, 75, 76, 79, 80, 83, 85, 88, 91, 93, 95, 97-104) . Reasons for exclusion from metaanalyses included; findings were only presented as correlation coefficients (n=16) (35, 54-56, 61, 68, 77, 78, 81, 82, 84, 86, 87, 90, 92, 96) or as standardised regression coefficients (n=4) (57,64,89,94) , the exposure variable was presented as sodium density (n=2) (12,72) or 24-hr urinary sodium excretion was reported as sodium concentration (mmol/L) (74) or on a logarithmic scale (52,58) . Of the studies included in meta-analyses, 14 were from Asia (62,63,66,69,70,73,75,76,83,85,91,97,100,101) , eight from USA (10,11,59,60,71,88,102,103) , five from South and Central America (53,65,79,80,93) , four from Europe (9,67,…”
Section: Resultsmentioning
confidence: 99%
“…One study reported a weak positive correlation between sodium intake and WC (unadjusted) (78) , three studies adjusted for a range of covariates and reported positive associations between sodium intake and waist circumference (10,11,74) and one study reported a positive association between sodium density and abdominal obesity (12) . Two studies, both of which adjusted for a range of covariates (57,58) , reported null findings and the final study reported mixed findings, with no relationship between sodium density and waist circumference, yet a positive association between sodium density and abdominal obesity (72) .…”
Section: Systematic Review Findings: Waist Circumference And/or Abdommentioning
confidence: 86%
See 3 more Smart Citations